National Capability Data: Annual Series, 1950-1988 - Taylor, Charles Lewis ([Verlag nicht ermittelbar], 1993)
This collection contains economic, military, and population indicators for 155 countries during the years 1950-1988. There are 2 identification and 15 substantive variables, which include size of armed forces, military expenditure, crude steel production, energy consumption, urban and total population, real gross domestic production (RGDP), and percentage share of RGDP in consumption, investment, and government.